Synthesis of Modified Polycarboxylate and Its Application in Ultra-High Performance Concrete - Xiang, Shuncheng; Tan, Yansheng; Gao, Yingli (Frontiers in Materials, 2021)
Modified polyurethane prepolymer was prepared using segmental synthesis method. Then, pectiniform polycarboxylate were synthesized at normal temperature in the complex initiation system of H2O2, APS, sodium bisulfite, Vc, and rongalit according to free radical polymerization reaction mechanism, using TPEG, AA, PEG as raw materials and TGA as chain transfer agent. Compared with commercial Sika polycarboxylate, their flowability, strength, drying shrinkage, auto-shrinkage were studied. The experimental results show that the synthesized polycarboxylate could be better dispersed. Adding silica fume can enhance the compressive strength of UHPC, while slag may decline its strength. By incorporation of slag and silica fume, the drying shrinkage of UHPC was reduced, but its auto-shrinkage was increased.